DNV ICAEW Seminar recording 14-11-19 - Aled Jones; Felicity Clarke; Rupert Read; Victor Anderson; Tom Maddox (Anglia Ruskin University, 2020)
These videos were taken at a seminar hosted by ICAEW, as part of the
Debating Nature's Project, on 14 November 2019.
The speakers are Deepak Rughani and Dr Tom Maddox.
These seminars encourage those involved in accounting to engage in the
debate around valuations of natural capital.
Keywords: 150106 Sustainability Accounting and Reporting; 160605 Environmental Politics